Joss Whedon, Dr. Horrible, and the Future of Web Media - Leaver, Tama (Routledge, 2013)
In the 2007 Writers Guild of America strike, one of the areas in dispute was the question of residual payments for online material. On the picket line, Buffy creator Joss Whedon discussed new ways online media production could be financed. After the strike, Whedon self-funded a web media production, Dr. Horrible's Sing-Along Blog. Whedon and his collaborators positioned Dr. Horrible as an experiment, investigating whether original online media content created outside of studio funding could be financially viable. Dr. Horrible was a bigger hit than expected, with a paid version topping the iTunes charts and a DVD release hitting the number two position on Amazon. This article explores which factors most obviously contributed to Dr. Horrible's success, whether these factors are replicable by other media creators, the incorporation of fan labor into web media projects, and how web-specific content creation relates to more traditional forms of media production.